PENGARUH KEMAMPUAN MEMAHAMI SOAL AKUNTANSI DAN PERSEPSI SISWA TENTANG METODE MENGAJAR GURU TERHADAP HASIL BELAJAR AKUNTANSI - Mellawati Mellawati; Yon Rizal; Tedy Rusman (JEE (Jurnal Edukasi Ekobis), 2013)
Purpose of this study was to determine the effect of accounting and the ability to understand students' perceptions about the teaching methods of teachers about the learning outcomes of the accounting sub adjusting entries subject x grade students majoring in accounting SMK N 1 Metro school year 2012/2013. The population in this study were all students of class X of accounting majors SMK Negeri 1 Metro Academic Year 2012/2013 the number of students 94 students by the number of samples based on the formula T. Yamane as many as 76 students were taken with probability sampling technique using a simple random sampling of the next allocation of proportional sampling that samples taken more proportional. The method used in this research is descriptive research approach to verification with ex post facto and survey.Teknik data analysis using simple linear regression and multiple linear regression. The problem in this research is the ability to understand there is a positive effect of accounting problems and perceptions of teachers' methods of teaching students about the learning outcomes of the subject sub accounting adjusting entry accounting majors class X students of SMK Negeri 1 Metro Academic Year 2012/2013?. Based on the analysis of the obtained results show that: 1). There is a positive and significant ability to understand the problem of accounting for the results of sub-subject study accounting adjusting entry accounting majors class X students of SMK Negeri 1 Metro Academic Year 2012/2013. 2). There is a positive and significant influence on students 'perceptions of teachers' teaching methods on learning outcomes of the subject sub accounting adjusting entry accounting majors class X students of SMK Negeri 1 Metro Academic Year 2012/2013. 3). There is a positive and significant accounting and the ability to understand the questions about the students' perceptions of teachers teaching methods on learning outcomes of accounting students of class X of accounting majors SMK Negeri 1 Metro Academic Year